ABSURDITAS ALBERT CAMUS DALAM NOVEL TERJEMAHAN KARYA ZURIYATI MENCARI PEREMPUAN YANG HILANG - Ari Khairurrijal Fahmi (Universitas Indraprasta PGRI, 2019)
Abstract: The aim of this study is to describe depthly about an Albert Camus Absurdity in a translation novel by Prof Zuriyati